Enhanced catalytic activity and near room temperature gas sensing properties of SnO2 nanoclusters@mesoporous Sn(iv) organophosphonate composite12. Issue 26 (26th June 2017) - Borah, Suchibrata; Bhattacharyya, Bagmita; Deka, Jumi; Borah, Aditya; Devi, Anuchaya; Deka, Dhanapati; Mishra, Shashank; Raidongia, Kalyan; Gogoi, Nayanmoni
Abstract : A simple route for preparing SnO2 nanoclusters embedded on mesoporous Sn(iv ) organophosphonate framework is described. Abstract : A simple, facile and one-pot route for preparing SnO2 nanoclusters embedded on a mesoporous Sn(iv ) organophosphonate (MSnP) framework is described. Reaction of SnCl4 ·5H2 O with a flexible tris-phosphonic acid, mesityl-1, 3, 5-tris(methylenephosphonic acid), in the presence of a surfactant under hydrothermal conditions produced the desired nanocomposite, SnO2 @MSnP. Analytical, spectroscopic and microscopic studies establish that SnO2 @MSnP composite is comprised of SnO2 nanoparticles of an average size of 5 nm evenly and abundantly dispersed over the MSnP framework. The mesoporous metal organophosphonate support significantly augments the catalytic efficacy and vapor sensitivity of SnO2 nanoparticles. The catalytic efficiency of SnO2 @MSnP was tested for two acid-catalyzed reactions: deoximation reaction and esterification of fatty acids. SnO2 @MSnP exhibits remarkable sensitivity towards ammonia and acetone vapors at near room temperature and under open atmospheric conditions. The present method represents an important step towards preparation of mesoporous metal organophosphonate supported metal oxide nanoclusters and hence offers easy access to functional metal oxide based nanocomposites.